PERBANDINGAN PEMBERIAN EDUKASI VERBAL DAN TERTULIS DENGAN TERTULIS TERHADAP KEPATUHAN PASIEN PASCA ODONTEKTOMI DI RSGM PROF SOEDOMO - , PUTRI SEPTIKA WATI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
C with medi flap and b teeth. Pati behavior c one of the compare complianc T into 2 grou while the of patient later when exact test. T = 0.041). than writte between c complianc Compliance ical or healt bone reduct ient complia coincides w e efforts in the verbal ce post odon This is quas ups. Written written gro compliance n the sample The results s Verbal and en educatio compliance ce than writt define as t th care. Odo ion around ance post od with a serie n improving and writte ntectomy pa i-experimen n verbal gro oup (n = 18 e post odon e did contro showed an a d written e on ( = 5,61 and educat ten educatio the extent to ontectomy i the tooth a dontectomy es of post o g patient co en educatio atient comp ntal study, p oup (n = 18 ) received o ntectomy us ols. Data we association ducation pr 1). The conc tion with wr on. o which a p is tooth extr and root bef y define as t odontectomy ompliance. T on with wr liance in th performed o 8) are educa only written sing questio ere analyze between ed roduces bet clusion of t ritten verba personâs be raction with fore using p the extent to y instructio The aim of ritten educ e RSGM Pr on 36 samp ated verball n education onnaires fill d statistical ducation wit tter compli this study is al education havior coin h mucoperio pliers to pu o which a p ons. Educati f this study cation to p rof. Soedom ples who div y and in wr nal. Measure ed out one lly using Fi th complian iance ( = s the relatio n produces b ncides osteal ull the person ion is is to atient mo. vided ritten, ement week sher's nce (p 7.61) onship better